Japa, or to flee or to run: Nigerian youth and the urgency of departure - Liu, Jing Jing (My University, 2023)
‘Japa’, a Yoruba term for ‘to run’ or ‘to flee’, has become part of the everyday vernacular of Nigerian youth since seizing the national imagination in 2020. While migration has always been a part of Nigerian culture, this paper asks, how did it become charged with such urgency? Casting migration as an act of ‘fleeing’ implies its necessity for survival. Why has this imagery, more readily associated with refugees or asylum seekers, been taken up by middle-class youth to express their desires to leave? Drawing on a series of interviews with Nigerian youth who are planning to leave or have left the country as education migrants, this paper traces the political, economic, and social configurations that weave urgency through the social-cultural phenomenon of japa.
Keywords: Nigeria; youth; education; migration; japa